Utilization of Dried Okara as a Flour Mixture of Bread-making - Violin Paramita; Agung Permana Budi (Institut Pariwisata dan Bisnis Internasional, 2015)
Soybean residue (Okara) is a good material which be reused and it has been described as having a great potential ingredient and higher economic value, such as dried Okara. Dried Okara has a component that can still be maintained, more durable and can be formulated and processed into a variety of bakery products. This study aims to understand the utilization of dried Okara as a flour mixture of bread-making. Product research and development conducted on March-May 2015 at International Bali Institute of Tourism Pastry and Bakery Kitchen Laboratory. The research method used is the ADDIE Model, namely: Analysis, Design, Development, Implementation, and Evaluation. Implementation of research is done through Phase: 1) Collecting the recipes, 2) Selection of recipe, 3) Design of the product, 4) Products manufacture test, 5) Assessment by panelists, 6) Evaluation. Assessment by panelists is made using an instrument test, which then performed the data analysis. Data analysis was performed by calculating the score given by the panelists based on texture, taste, color and aroma. The results obtained were: Utilization of 10% dried Okara has the highest score, 82.8% of the expected, so the maximum amount of dried Okara as a flour mixture is 10% of the flour used in bread-making.